Weight performance of lambs under three production systems - de Ávila, Volney Silveira (2021)
This experiment was conducted to evaluate the effects of three production systems on the weightgain of Ille de France male lambs within 15 to 20 days of age for a period of 63 days. The animals were assigned to complete randomized design in three treatments (T). In T1, 10 animals were kept with their mothers in an area of ryegrass paddock without supplementation. In T2, 8 animals were kept in confinement and feeding withconcentrate in pellets with 22% GP and whole ryegrass at will. Also they had access twice a day to their mothers’milk . In T3, 10 animals were kept together with their mothers in a ryegrass pasture with free access to creepfeeding with concentrate in pellets with 22% GP. The T2 got higher (P < 0,05) live weight gain than T1 and T3 in the period between 33 and 64 days of age. There was no significant difference (P > 0,05) in the periods of 17-32 days and 65-80 days of age between T2 and T3 treatments, but they differ from T1. The gross margins obtainedwere of R$ 54.25; R$ 85.86 and R$ 66.99 for treatments 1, 2 and 3 respectively